Characterization of Erythroferrone in a Teleost Fish (Dicentrarchus labrax) With Two Functional Hepcidin Types: More Than an Erythroid Regulator - Neves, João V.; Barroso, Carolina; Carvalho, Pedro; Nunes, Magda; Gonçalves, José F. M.; Rodrigues, Pedro N. S. (Frontiers in Immunology, 2022)
Erythroferrone is a recently identified erythroid regulator produced by erythroblasts in the mammalian bone marrow and extramedullary sites, known to be induced in conditions of anemia or blood loss. Iron metabolism is affected by erythroferrone through its capacity to inhibit hepcidin production, leading to the increase of iron availability required for erythropoiesis. However, little is known about erythroferrone function in other vertebrates, in particular teleost fish, that unlike mammals, present two different functional types of hepcidin, one type mostly involved in iron metabolism and the other in antimicrobial response. The study of erythroferrone evolution and its biological role in teleost fish can give us valuably new insights into its function. To address these questions, we characterized erythroferrone in the European sea bass (Dicentrarchus labrax), a species presenting two hepcidin types, and evaluated variations in its expression levels in response to different experimental conditions. During experimental anemia, erythroferrone responds by increasing its expression and suppressing hepcidin production, following the pattern observed in mammals, but it is not influenced by iron overload. However, during bacterial infection, erythroferrone is downregulated and hepcidin levels increase. Furthermore, administration of Hamp1 but not of Hamp2 peptides suppresses erythroferrone expression. In conclusion, in dual hepcidin teleost fish erythroferrone seems to only interact with type 1 hepcidin, known to be involved in iron homeostasis, but not with type 2, which has an almost exclusive antimicrobial role.